MARKETING STRATEGY ANALYSIS ON THE PERCEPTION OF PARENTS IN CHOOSING AN INTEGRATED ISLAMIC ELEMENTARY SCHOOL FOR THEIR CHILDREN IN PALEMBANG - delta khairunnisa (Jurnal Ilmiah Econosains, 2019)
The purpose of this study was to determine the perception of parents in choosing a school Basic Islamic Integrated (SDIT) for their children and to see how the strategy marketing carried out by the Integrated Islamic Elementary School (SDIT). Data collection is done by distributing questionnaires using 4 Likert scales. This study used purposive sampling. The analysis technique used is inference analysis which uses multiple regression tests. Research result shows that the development of marketing strategies for schools that needs to be improved is the cost of education, promotion activities carried out by the school and the process of new student recruitment, while the variable that is maintained is the quality of the students, school facilities and infrastructure, human resources, and customer service.